Nonlinear Pricing under a Balanced-Budget Requirement: The Two-Type Case - Tommy Andersson (Lund University, School of Economics and Management, Department of Economics, 2004)
An economy consisting of two different types of consumers and one publicly owned natural monopoly is under consideration. The preferences of the consumers are assumed to be linear in money and the demand curves are assumed not to cross. We also suppose that the net utility from consumption is so high that we do not have to consider the individual rationality constraints. Given these assumptions, we completely characterize the set of budget-balanced and Pareto efficient nonlinear pricing schedules. This complete characterization has not been presented in the literature before.
Keywords: D63; D82; H40; 330; Nonlinear Pricing; Budget-Balance